Memórias das aritméticas da Emília: o ensino de aritmética entre 1920 e 1940 - Oliveira, Adriel Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research claims to investigate how practices of arithmetic teaching manifest explicitly in the fictional work Aritmética da Emília, by the brazilian writer Monteiro Lobato (1882 - 1948). Besides, it dialogues to tracks of others cultural practices the mentioned book can point to, based on the historical context of mathematical teaching between 1920 and 1940. Our analysis follows to intertextuality methods between a several documents from this period, such as A Aritmética da Emília (1935, 1° edition, 1939; 2° edition; 1942, 3° edition; 1944, 4° edition), Aritmética da Emília (1947); others works made by Lobato; arithmetics books written at that time; laws about teaching; letters between Lobato and Anísio Teixeira; letter between Lobato and Julio Cesar de Mello e Souza; magazines on teaching; texts on decades 1920 and 1940 education; youth literature books. We have as a reference Chartier, Burke and Ginzburg. We concluded that Aritmética da Emília shows all philosophical and pedagogical contradiction of those years, confronting the didactic tradition of conservative education with the renewal movement of the New School, swinging the innovative nature of its pedagogical proposal and falling in pratices professorial of those times

Esta pesquisa objetiva investigar como práticas de ensino de aritmética se manifestam explicitamente na obra ficcional A Aritmética da Emília, do escritor brasileiro Monteiro Lobato (1882 - 1948), e a que rastros de outras práticas culturais o referido livro pode arremeter, com base no contexto de ensino de matemática compreendido entre 1920 e 1940. Para tanto, nossa opção de análise segue a intertextualidade entre alguns documentos da época, tais como A Aritmética da Emília (1935, 1° edição, 1939; 2° edição; 1942, 3° edição; 1944, 4° edição), Emília no país da Gramática e Aritmética da Emília (1947); outras obras de Lobato; livros didáticos de aritmética da época; Legislação sobre ensino; cartas entre Lobato e Anísio Teixeira; carta entre Lobato e Julio Cesar de Mello e Souza; revistas sobre ensino; textos sobre educação daquela época; livros de literatura infantil. Temos por referenciais Guinzburg, Chartier e Burke. Concluimos que A Aritmética da Emília reúne em si todas as contradições filosóficas e pedagógicas daquela época, confrontando a tradição didática do ensino conservador com o movimento renovador da Escola Nova, oscilando o caráter inovador de sua proposta pedagógica e recaindo nas práticas professorais de sua contemporaneidade
Keywords: Lobato, Monteiro, 1882-1948; Mathematics - History; Literatura infantojuvenil; Matemática - História; Aritmetica - Estudo e ensino; Aritmetica - 1920-1940; Positivismo; Escola nova; Matemática - Estudo e ensino